The pirates of Penzance - Sullivan, Arthur 1842-1900; Gilbert, William S. 1836-1911 (Kultur, 1994)
Gilbert and Sullivan's hillarious operetta tells the story of an orphan named Frederic. The son of a wealthy 19th century man, his fate takes a sudden twist after his father's death